Relationship between cardiovascular fitness and academic achievement among medical students of Udayana University in batch 2018 - Dashinnie Narasimhanaidu; I Nyoman Gede Wardana; I Nyoman Mangku Karmaya (DiscoverSys Inc., 2020)
Background: Physical fitness especially cardiovascular fitness is one of the important factors in medical students’ academic achievement which has been neglected by majority of the students. Through cardiovascular fitness the stress level could be reduced which will eventually help the students to achieve better academic results.Aim: This study aims to determine the relationship between the cardiovascular fitness and academic achievements by medical students of Medical Faculty of Universitas Udayana from batch 2018.Method: An experimental survey method has been used identify the relationship between cardiovascular fitness level and academic achievement. Respondents who attended this study were 79 students from the batch 2018. The cardiovascular fitness level will be measured by Fartlek training which is conducted in medical faculty campus parking area. The students’ academic achievement will be measured through their 1st biomedic exam results. Then, the pulse rate collected from the Fartlek training and the academic achievement from exam was compared to identify the relationship the cardiovascular fitness and academic achievement.Results: The data was not normally distributed from the normality test. Spearman’s rho test shows that the data is not significant with the (p = -0.056).Conclusion: There was no significant relationship between the level of cardiovascular fitness and the academic achievement of the medical students.